UPAYA REMAJA MASJID AL-MU’MININ DALAM MENINGKATKAN PENDIDIKAN AGAMA ISLAM DI DUSUN TEMPUKUNG DESA TEMPATAN KECAMATAN SEBAWI KABUPATEN SAMBAS - Semawati Semawati (Tarbiya Islamica, 2016)
The purpose of this research is to reveal about:1) the efforts of Al-mu’minin mosque youth in improving Islamic Understanding in Tempukung Hamlet, Local Village, Sebawi District, Sambas Regency. 2) supporters and inhibitions of Al-mu’minin Mosque Youth in Improving Understanding of Islam in Tempukung Hamlet, Local Village, Sebawi District, Sambas Regency. This researcher uses a qualitative approach and a descriptive type. Data collection techninques using interviews, observation, and documentation. The data analysis techniques used are data collection, data reduction, data display, and conclusion drawing. The data validity techniques used are trigulation techniques, member checks and detailed description. Efforts made by Al-mu’minin mosque youth in increasing understanding of Islam in Tempukung Hamlet, Local Village, Sebawi District, Sambas Regency are conducting routine studies. The supporting factors for the youth of the Al-mu’minin mosque to improve their understandings of Islam in Tempukung Hamlet, Local Village, Sebawi District, Sambas Regency are mosque administrators, the community, and the presence of funds. The inhibiting factors such as the lack of self-awareness of adolescents, the existence of other activities, and the environment.